Antioxidant Potential and the Characterization of Arachis hypogaea Roots. (21st December 2019) - Ullah, Samee; Hussain, Syed Ammar; Shaukat, Faryal; Hameed, Ahsan; Yang, Wu; Song, Yuanda
Abstract : Arachis hypogaea roots are used as traditional Chinese medicine to treat different ailments, and the present study involves the exploration and comparison of phenolic profile and antioxidant activities (ABTS + and DPPH assay) of A. hypogaea root extract in different solvents. 70% aqueous acetone and 70% aqueous ethanol were proved to be the best solvents to recover total phenolic compounds, with a yield of 42.59 ± 1.96 and 41.34 ± 0.92 mg/g dry weight of extract, respectively. ABTS + radical scavenging activity was the highest in 70% aqueous ethanol, while the absolute methanol extract showed the highest DPPH radical scavenging activity (29.50 ± 2.19 μ g/mL). Furthermore, phytochemical profiling of 70% acetone extract of A. hypogaea roots was performed by LC-ESI-TOF-MS analysis which in turn indicated the presence of diverse compounds in the A. hypogaea root extract, namely, quinones, stilbenoids, and flavones and flavonoid glucosides.